Effects of human crowding and the physical attractiveness of others on customers in stores. Issue 1 (2nd January 2017) - Jung, Hyein; Baek, Eunsoo; Choo, Ho Jung
ABSTRACT: This study examines how the physical attractiveness of other customers affects consumer emotions and behaviors in the context of human crowding in a fashion store. We propose that consumers' store avoidance behaviors due to human crowding are affected by the physical attractiveness of other customers, and explain the mechanism as pleasure based on the S-O-R model. With a 2 (crowding level: high vs low) × 2 (physical attractiveness of other customers: high vs low) ANCOVA of 3D virtual stores, a lab experiment was conducted. Data from a total sample of 137 females was analyzed using SPSS 18.0. Analysis of variance and moderated mediation were performed. Results provide empirical insights about the interactive effect of store crowding and physical attractiveness of other customers on in-store customers' avoidance behavior, which is mediated by pleasure. Findings enrich the existing literature on store crowding and provide both theoretical and managerial implications.